Anion binding by receptors containing NH donating groups – What do anions prefer?. (13th August 2022) - Barišić, Dajana; Lešić, Filip; Tireli Vlašić, Martina; Užarević, Krunoslav; Bregović, Nikola; Tomišić, Vladislav
Abstract: Understanding the interplay between host structure and its ion-binding ability is one of the fundamental tasks in host-guest chemistry, as this allows prediction of their behaviour as supramolecular receptors. We tackled this issue in the present work by studying a series of aromatic amide derivatives and a hybrid urea-amide derivative as anion receptors in DMSO by 1 H NMR and UV–Vis titrations. We found that the amide derivatives formed complexes of 1:1 stoichiometry with the tested anions (H2 PO4 −, AcO −, Cl − ) and that both amide NH-groups were involved in the anion coordination. Spectral changes accompanying the complexation reaction also revealed that certain aromatic CH groups acted as hydrogen-bond donors aiding the complex stabilisation. In the cases of acetate or chloride, the hybrid urea-amide receptor 6 H bound one anion engaging only the urea group as the binding site. In contrast, when dihydrogen phosphate was added to 6 H the 1:1 and 2:1 complexes (anion:receptor) were detected. Again, the 1:1 complex was stabilized only by H-bonds with urea as the binding site. On the other hand, in the case of complex comprising two anions, the amide group participated in stabilisation and strong interanionic hydrogen bonds were formed. The gathered results addressed the title question, revealing that simple anions prefer to bind to urea when offered an amide or urea groups as binding sites without significant steric constraints. However, the presence of an amide group can facilitate the formation of higher complexes in specific cases. Graphical abstract: Image 1